Urolithin A Promotes Angiogenesis and Tissue Regeneration in a Full-Thickness Cutaneous Wound Model - Zhen-hua Feng; Zhen-hua Feng; Jia Chen; Jia Chen; Pu-tao Yuan; Pu-tao Yuan; Zhong-yin Ji; Zhong-yin Ji; Si-yue Tao; Si-yue Tao; Lin Zheng; Lin Zheng; et al. (Frontiers Media S.A., 2022)
The treatment of chronic wound is an important topic of current clinical issue. Neovascularization plays a crucial role in skin wound healing by delivering fresh nutrients and oxygen to the wound area. The aim of this study was to investigate the mechanisms of urolithin A (UA) in angiogenesis during wound healing. The results of in vitro experiments showed that treatment with UA (5-20 μM) promoted the proliferation, migration, and angiogenic capacity of HUVECs. Furthermore, we investigated the effect of UA in vivo using a full-thickness skin wound model. Subsequently, we found that UA promoted the regeneration of new blood vessels, which is consistent with the results of accelerated angiogenesis in vitro experiments. After UA treatment, the blood vessels in the wound are rapidly formed, and the deposition and remodeling process of the collagen matrix is also accelerated, which ultimately promotes the effective wound healing. Mechanistic studies have shown that UA promotes angiogenesis by inhibiting the PI3K/AKT pathway. Our study provides evidence that UA can promote angiogenesis and skin regeneration in chronic wounds, especially ischemic wounds.